Social Engineering To Floating Net-Cage Fish Farmers In Ranu Klakah Lumajang, East Java - Yuni Kilawati; Yunita Maimunah; Adharul Muttaqin; Attabik Mukhammad Amrillah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2023)
Apart from being a tourist destination, Ranu Klakah, is also used as a fishing business location for capture and aquaculture. Local people use it as a place for fish farming using the floating net cage (KJA) method which has quite a large potential. Currently problems faced by floating net cage fish farmers in Ranu Klakah is the unavailability of adequate fishery facilities and infrastructure, both fisheries and aquaculture, the low application of fishery technology in the field of aquaculture and marketing of fishery products and the low quality of human resources for fisheries sector business. These solutions, aimed to improve community knowledge about best management practice of aquaculture using floating net-cage system, increasing community knowledge about digital product marketing and improving the quality and quantity of fish production in floating net cage systems in Ranu Klakah to attract consumers with wider coverage area and high time flexibility.